ANALISIS SEGMENTASI PASAR BERBASIS MARKETING MIX DALAM MENDUKUNG WISATA KULINER DI EDEN DAILY INTERNATIONAL FOOD DI KOTA SEMARANG - Ahmad Mansur (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2022)
The research carried out has the function of analyzing market segmentation based on marketing mix in supporting culinary tourism at Eden Daily International Food in Semarang City. This research was conducted because this restaurant is considered not maximal in supporting culinary tourism in the city of Semarang seen from the customers who are mostly from within the city of Semarang. With the problem, namely: "What are the strategies carried out by Eden Daily International Food in order to support Semarang culinary tourism, How to apply the marketing mix in Eden Daily International Food in order to support Semarang culinary tourism, How to analyze market segmentations in eden daily international food in order to support culinary tourism in Semarang This research was conducted using qualitative methods, with a sample of 11 informants, 1 owner, 5 Eden employees and 5 customers. The research data were obtained from observation, interviews, and documentation with open questions. The results of this research show that the strategy that Eden has implemented for its promotion has not been maximized properly, there are still deficiencies in the field of promotion, then the marketing mix has been maximized by seeing the several facilities it has, then the market segmentation that has been carried out is good, for example the price and product are in accordance .